New Classification of Benign Epithelial Tumors: Colorectal Polyps and Synchronous Neoplasms: An Update and Critical Assessment: An Analysis of 678 Consecutive Cases and 1137 Polyps - Ali KOYUNCUER; Tulay ZENGINKINET (Medeniyet Medical Journal)
Objective: We aimed to evaluate of colorectal high-risk polyps and synchronized neoplasms and carcinomas with anatomical localization and demographic characteristics. Methods: Between July 1, 2018 and July 1, 2022, 1137 polypectomy materials of 678 consecutive patients who were diagnosed in the pathology department and underwent total colonoscopy were included in the study. All epithelial polyps were re-classified according to the World Health Organization classification of digestive system tumors-2019, 5th edition. Results: The cases of 60.5% were male and 39.5% were female. The mean age of patients with polyps was 61.1 (+-11.1) years. There was a statistically significant difference between the presence of gender and all epithelial polyps (p=0.044). Epithelial polyps were more common in men than in women (ratio; male/female 1.58: 1). While the average size of the polyps was 5.2 (+-5.08) millimeters (mm), 86.6% of all polyps were smaller than 10 mm. Solitary polyps were observed in 62.5% of all polyps, and multiple polyps were observed in 37.5%. Epithelial polyps constituted 96% of all polyps, and conventional tubular adenoma (69%) was the most common type of polyp. Advanced adenomas (intramucosal adenocarcinomas, polyp cancer) and synchronous adenocarcinomas were found to be 1.4% (16 polyps) and 0.9% (6 patients) respectively. Polyps were most frequently observed in the sigmoid colon, with a rate of 22.8%, followed by the descending colon and rectum most frequently. There was a significant association between epithelial polyps and anatomical locations (p<0.001). Conclusions: In conventional colorectal adenomas, the frequency of co-occurrence of synchronous neoplasms is higher than in other polyp types.